SIDO coupled inductor‐based high voltage conversion ratio DC–DC converter with three operations. Issue 10 (31st May 2021) - Saadatizadeh, Zahra; Chavoshipour Heris, Pedram; Babaei, Ebrahim; Blaabjerg, Frede; Cecati, Carlo
Abstract: Here, a single‐input, dual output (SIDO) coupled inductor‐based high voltage conversion ratio DC–DC converter is proposed. The proposed converter has the capability of operating as a SIDO converter in a way that the terminal of the input voltage source is exchangeable among the three ports. Therefore, there are three different operation modes for the proposed converter. The voltage conversion ratios of the high voltage ports over the low voltage port can be improved by increasing the turn ratio of the coupled inductors. The main advantage of the proposed converter is achieving high voltage gains with lower number of components for the whole range of duty cycles comparing to the conventional multi‐port high voltage gain converters. Moreover, two output voltages of the proposed converter can be simultaneously regulated on different constant levels with a good precision. In this study, the voltage conversion ratios, the inductors' average currents, the voltage and current stress on the switches are calculated theoretically. Finally, an experimental prototype of 30 V input and 410, 260 V outputs with the power 510 W is implemented and the results are verifying the theoretical ones.